Genius loci, ovvero, regnare sull’autoctonia ed i suoi opposti - Ferreri, Emanuela (Mediascapes journal, 2018)
The main objective of the paper is to analyze the concept of autochthonous and exogenous origin as a cultural topic of structural importance, moving towards a universal consideration. The topic is obviously connected to the global process continuing to naturalize and/or historicize the social and cultural phenomenon of identity. Starting with recent public debates on jus soli/jus sanguinis, the paper explores international migration as the object and the subject of the sociological imagination of the future. The objective of the analysis is to describe socio-anthropological knowledge and research as a place of application and expression of a genius loci, inside intra, inter and trans-cultural understanding.